Want this question answered?
Be notified when an answer is posted
What do you want to convert it to? x2 + y2 = 2x If you want to solve for y: x2 + y2 = 2x ∴ y2 = 2x - x2 ∴ y = (2x - x2)1/2 If you want to solve for x: x2 + y2 = 2x ∴ x2 - 2x = -y2 ∴ x2 - 2x + 1 = 1 - y2 ∴ (x - 1)2 = 1 - y2 ∴ x - 1 = ±(1 - y2)1/2 ∴ x = 1 ± (1 - y2)1/2
You cannot solve it since only one side of an equation is given. If the equation was y4 + 5y2 - 84 = 0 then y4 + 12y2 - 7y2 - 84 = 0 or y2*(y2 + 12) - 7*(y2 + 12) = 0 or (y2 - 7)*(y2 + 12) = 0 then y2 = 7 or y2 = - 12 y = +or- sqrt(7) and, if you are in the complex domain, also y = +or- i*sqrt(12) where i is the imaginary square root of -1.
2x2-y2
Points: (x1, y1) and (x2, y2) Slope: y1-y2/x1-x2
Y²-5Y+4=0 Y1=-(-5/2) - Square root of ((-5/2)²-4) Y1= 2.5 - Square root of 2.25 Y1 = 1 Y2=-(-5/2) + Square root of ((-5/2)²-4) Y2= 2.5 + Square root of 2.25 Y2 = 4 Y can be either 1 or 4
What do you want to convert it to? x2 + y2 = 2x If you want to solve for y: x2 + y2 = 2x ∴ y2 = 2x - x2 ∴ y = (2x - x2)1/2 If you want to solve for x: x2 + y2 = 2x ∴ x2 - 2x = -y2 ∴ x2 - 2x + 1 = 1 - y2 ∴ (x - 1)2 = 1 - y2 ∴ x - 1 = ±(1 - y2)1/2 ∴ x = 1 ± (1 - y2)1/2
0
You cannot solve it since only one side of an equation is given. If the equation was y4 + 5y2 - 84 = 0 then y4 + 12y2 - 7y2 - 84 = 0 or y2*(y2 + 12) - 7*(y2 + 12) = 0 or (y2 - 7)*(y2 + 12) = 0 then y2 = 7 or y2 = - 12 y = +or- sqrt(7) and, if you are in the complex domain, also y = +or- i*sqrt(12) where i is the imaginary square root of -1.
4x-y2=2xy 2x ? y5 if its plus its 7 xy
2x2-y2
Well, darling, factorization is just a fancy term for breaking down an expression into its simplest parts. In this case, we have 8x + 26x - 7. Combine like terms to get 34x - 7. So, the factorization of 8x + 26x - 7 is simply 34x - 7. Easy peasy lemon squeezy!
Points: (x1, y1) and (x2, y2) Slope: y1-y2/x1-x2
if its 5x-34x=5 then its 5.8
Y²-5Y+4=0 Y1=-(-5/2) - Square root of ((-5/2)²-4) Y1= 2.5 - Square root of 2.25 Y1 = 1 Y2=-(-5/2) + Square root of ((-5/2)²-4) Y2= 2.5 + Square root of 2.25 Y2 = 4 Y can be either 1 or 4
The expression Y-2 is 1/Y2. The reciprocal of 1/Y2 is Y2.
y=±√15
There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).